Challenges and Strategies in Teaching English to Autism Spectrum Disorder at SLB Pelita Nusa Pekanbaru - Nadhila, Amalia; Mahdum; Afrianto (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
Teaching student with special needs could be complicated. This research aimed to define English teachers' challenges in teaching English to students with Autism Spectrum Disorder (ASD). This research was conducted at SLB Pelita Nusa Pekanbaru using qualitative methods within a case study research design. In-depth interviews with two English teachers, observation, and documentation were used as data collection techniques. Based on the results, teachers faced several challenges in teaching English to students with ASD that are closely related to the characteristics of the children themselves. The challenges could be regarding students' mood and emotional regulation issues, tantrums and behavioural issues, verbal communication barriers, short attention span and memory retention issues, students' repetitive and restricted behaviour, lack of motivation, and external factors such as parental influence. To address these issues, teachers used various strategies such as repetition in learning, using visual aids and technology, simplifying the instructions, adjusting the phase of learning, and collaborating with the parents. This research provides practical insight into teaching English to students with ASD. It highlights the necessity for teachers to be patient, creative, adaptive, and collaborative when teaching English to students with ASD.